Effects of cashew gum and nanoparticles on cooled stallion semen - Kahynna Cavalcante Loureiro; Isabel Bezerra Lima-Verde; Anders Johannisson; Theodoros Ntallaris; Alessandro Jager; Petr Štěpánek; Marcelo da Costa Mendonça; Patrícia Severino; Jane M. Morrell (Acta Veterinaria Scandinavica, 2020)
Abstract Background Cryopreservation of stallion spermatozoa tends to cause plasma membrane damage due to the low ratio of cholesterol to phospholipids. Gums have been suggested as an alternative cryoprotectant to glycerol for stallion spermatozoa. Therefore, the present experiment was designed to verify whether the effect of addition of cashew gum (CG), or nanoparticles (NP) containing CG, to the extender before cooling on sperm quality in stallion semen. Ejaculates from 6 stallions were extended and split between six treatment groups (control, a-tocopherol [TOC], CG1, CG0.5, NP1 and NP0.5), stored in cryotubes at 4 °C. Results Aliquots were analysed by computer-assisted sperm motility analysis on the day of collection, and after 24 h and 48 h of cold storage. After 48 h, the total motility with NP1 (78.53 + 6.31%) was similar to control 85.79 + 6.31% at 0 h. The same pattern was observed for progressive motility. Membrane integrity assessed by flow cytometer was similar between control, TOC and G1 at all storage times. The DNA fragmentation in the control group increased at all time points, whereas chromatin integrity was maintained after 24 h in TOC and NP0.5 compared to 0 h. There was no increase in the proportion of live spermatozoa producing hydrogen peroxide, but there was a tendency for an increased proportion of spermatozoa in the live superoxide category in CG1 after 24 h cooled storage. Conclusions The addition of CG or CG-derived NP to extender for stallion semen was not harmful to the sperm cells.